ENERGY PRICES AND INFLATIONARY PRESSURE IN NIGERIA - Ibeinmo Friday Cookey; Kelvin Chinaka Njoku; Uwuma Chidi (PT. Antis International Publisher, 2026)
Objective: This study determines the effect of energy prices on inflationary pressure in Nigeria using time series data from 1990 to 2024. Method: Inflationary pressure was measured by inflation rate while proxies of energy prices adopted include electricity price, premium motor spirit price, natural gas price and solar energy price). The time series data used for the study were sourced from International Energy Agency (IEA), National Bureau of Statistics (NBS) and Central Bank of Nigeria (CBN) Statistical Bulletin. The model was estimated by Augmented-Dickey Fuller (ADF) test, bounds cointegration test and Autoregressive Distributive Lag (ARDL) approach while the data analysis was facilitated by EViews 12.0 statistical software. Results: The findings of the study showed that electricity price, premium motor spirit and natural gas price have positive and significant effects on inflation rate in Nigeria while solar energy price has a positive and non-significant effect on inflation rate in Nigeria. The study concluded that energy prices contribute significantly to inflationary pressures in Nigeria. Novelty: The study recommended that government should adopt a more targeted subsidy framework that focuses on low-income households and small businesses. This will reduce the inflationary effect of energy price hikes while preventing fiscal leakages and ensuring price stability in essential energy markets.